Study of magnesium precipitation based on biocementation. Issue 10 (26th November 2019) - Sun, Xiaohao; Miao, Linchang; Wu, Linyu; Wang, Chengcheng
Abstract: Magnesium carbonate has a cementing character like calcium carbonate, and the addition of magnesium ion enables the microbe cementitious material to have the denser microstructure with the lower porosity. The effects of various factors, such as the concentration of Ca 2+ and Mg 2+, on the urease activity were studied. Comparison of the productive rates for calcium carbonate and magnesium carbonate were carried out, as well as productive rates for magnesium carbonate with adding different amount of urea to medium. Calcium acetate and magnesium acetate were, respectively, used for sands solidification. Results showed that the increase in urea concentration and magnesium ion enhanced urease activity, while calcium ion significantly impaired urease activity. Sodium chloride and acetate ion had little influence on it. Productive rates for magnesium carbonate were dramatically smaller than its calcium counterpart. However, adding urea to medium allowed for more magnesium precipitation, and the higher the urea concentration, the more the magnesium precipitation. The sand columns with adding urea to medium can have a high strength despite using magnesium acetate. Therefore, the method could solve the problem of insufficient magnesium precipitation. The results will act as a guide for the application of biocementation technology with magnesium carbonate.